In-situ growth of mesoporous Nb2O5 microspheres on g-C3N4 nanosheets for enhanced photocatalytic H2 evolution under visible light irradiation. (9th March 2017) - Huang, Qun-Zeng; Wang, Ji-Chao; Wang, Pan-Pan; Yao, Hong-Chang; Li, Zhong-Jun
Abstract: Large-surface-area mesoporous Nb2 O5 microspheres were successfully grown in-situ on the surface of g-C3 N4 nanosheets via a facile solvothermal process with the aid of Pluronic P123 as a structure-directing agent. The resultant g-C3 N4 /Nb2 O5 nanocomposites exhibited enhanced photocatalytic activity for H2 evolution from water splitting under visible light irradiation as compared to pure g-C3 N4 . The optimal composite with 38.1 wt% Nb2 O5 showed a hydrogen evolution rate of 1710.04 μmol h −1 g −1, which is 4.7 times higher than that of pure g-C3 N4 . The enhanced photocatalytic activity could be attributed to the sufficient contact interface in the heterostructure and large specific surface area, which leads to effective charge separation between g-C3 N4 and Nb2 O5 . Highlights: The composite was prepared by in-situ loading Nb2 O5 microspheres on g-C3 N4 surface. Sufficient contact interface between g-C3 N4 and Nb2 O5 is achieved. The composite possesses large specific surface area and abundant mesopores. The heterojunction effectively promotes the transfer and separation of e − and h + . The composite exhibits enhanced photocatalytic activity for H2 evolution.